A New Meta-heuristic Technique Based on Robust Power System Stabilizer with Wind Power Penetrations - Vahid Sattarpoor; Homayoun Ebrahimian (Institute of Advanced Engineering and Science, 2015)
In this paper a robust Power System Stabilizer (PSS) is proposed based on inverse additive perturbation in a power system with wind farms. The proposed controller designed by new Improve Bacteria Foraging Algorithm (IBFA) to achieve robustness of this strategy where the optimization process is formulated based on an enhancement of system robust stability margin. The designed optimal PSS is based on Fuzzy Logic Controller (FLC). The effectiveness of the proposed technique is tested over ten macine 39 buses New England power system. Obtained results demonstrate the superiority of proposed technique over conventional PSS.